Population dynamics and resource utilization of the lesser grain borer, Rhyzopertha dominica (F.) - Nguyen, Valerie (Kansas State University, 2022)
Genomic tools can provide important insights into the biology, dispersal, and feeding habits of insects whose behavior is difficult to monitor in the field, including stored product insects that primarily attack dried stored commodities and disperse throughout different agricultural landscapes where they may feed on alternate food resources. The lesser grain borer, Rhyzopertha dominica (Coleoptera: Bostrichidae), is a cosmopolitan pest that primarily attacks stored grain, but can be found in prairie landscapes despite the lack of primary food hosts in these natural locations. The presence of R. dominica in natural landscapes surrounding grain storage structures suggests that there could be interactions between individuals that colonize these habitats. In addition, lab studies have shown that this insect can feed and develop on alternative food hosts found in prairie landscapes. This thesis investigates the local interactions between populations of R. dominica at grain storage facilities and a nearby tallgrass prairie over the course of three field seasons using population genomics and dietary habits of R. dominica from two different tallgrass prairies (Nine Mile Prairie, Lincoln, NE and Konza Prairie, Manhattan, KS) using molecular gut content analysis . The population structure of R. dominica was examined by generating single nucleotide polymorphisms for individuals over three years to determine the interactions between insects caught in a large-scale grain elevator, a research flour mill, and a native tallgrass prairie. All three locations were located within 10 miles of one another. Heavy admixture was observed between the three locations across all three years surveyed, and location, field season, and the interaction of these two variables failed to explain the majority of the variation in genotypic diversity found in this species. In fact, more variation was observed among insects caught within a single location relative to insects collected from different locations. The most divergent populations were observed in the 2019 field season, likely due to the high amounts of rainfall observed and the lower number of individuals caught during this field season. The population of insects caught in the flour mill was also the most dissimilar to the flour mill and the prairies, which can be attributed to the strict guidelines for pest prevention in these types of facilities. The heavy admixture observed between the three locations, coupled with the low genetic variation between the locations, suggests significant interactions between these populations and indicates that R. dominica may be able to migrate between sources of grain and natural landscapes. To identify gut contents of R. dominica from Konza Prairie and Nine Mile Prairie, beetles were collected during their active flight season and plant-specific rbcL primers were used to detect and taxonomically classify plant DNA found inside the insect guts. Overall, we were able to identify 57 unique plant sequences between the two locations and identify 27 different plant species within their guts. While some individuals at both locations had recently fed on stored product commodities, products derived from these hosts were in low abundance. The most common and abundant taxon found in guts of insects caught in both locations was classified as Thinospyrum ponticum, which is known as tall wheatgrass. Several other plant species that are native to both the Konza and Nine Mile Prairies were identified, suggesting that R. dominica is able to exploit natural resources. The results from both studies highlight that R. dominica can exploit natural resources found in prairies and those that insects caught innatural landscapes near grain storage facilities interact with one another. These results contribute an increase in the understanding of the population dynamics of R. dominica between grain storage and the natural environment at a local scale, as well as their resource utilization. Previous studies have shown that populations in grain storage facilities can rebound quickly after fumigation and that insects in the surrounding landscape may serve as source populations. Our study confirms that insects from grain storage facilities and flour mills interact with those found in adjacent habitats. Therefore, we can use these results to better inform pest management and prevention of infestations by accounting for beetles that migrate from natural landscapes. Future work should assess gut content structure of R. dominica found in grain storage in comparison to those caught in landscapes, as well as assess genetic population structures across other location types and systems to gain further insights into their movement and migration.
Keywords: Stored product entomology; Molecular entomology; Konza Prairie; Lesser grain borer; Diet